Comparative Outcomes of Video vs. Direct Laryngoscopy in Adults in Critical Condition: A Narrative Review of First-Attempt Success, Complications, and Contextual Decision-Making - Cristian Camilo Villa Gómez; Camilo Hernández Ortiz; Julio Andrés Boda Garnica; Omar Andrés Olea Muñoz; Daniela Giraldo Restrepo; Angie Marcela Pérez Pinto; Marlon Andrés David Orrego; Luisa Fernanda Herrera Aguirre; Gustavo Adolfo Serrano Baez (Iberoamerican Journal of Medicine)
Tracheal intubation emerges as a fundamental medical procedure for critically ill patients, facilitating the establishment of a secure airway and ensuring adequate oxygenation and ventilation. This narrative review compares video laryngoscopy (VL) and direct laryngoscopy (DL) in critically ill adults, evaluating three key parameters: first-attempt success rates, incidence of severe complications (hypoxemia, hemodynamic instability), and contextual factors influencing technique selection (patient anatomy, operator expertise, resource availability). Literature review found that challenges frequently arise in critically ill patients, influencing their respiratory, cardiovascular, and neurological systems. The primary techniques for tracheal intubation include DL and VL. Various studies have compared these techniques across diverse clinical scenarios. While some studies suggest potential advantages of VL, such as higher first-attempt success rates, others report no significant disparities. These findings underscore the inherent complexities in decision-making. To make an informed choice, considerations must include patient anatomy, operator experience, equipment availability, continuous monitoring, and adherence to clinical guidelines. Thus, the determination between DL and VL for intubating critically ill patients is multifaceted. Individual patient assessment, clinician proficiency, and resource accessibility are of paramount importance. Adherence to best practices and the ability to dynamically adapt to unforeseen challenges are critical aspects. Patient safety remains the highest priority, and these strategies provide a comprehensive framework for informed decision-making in critical scenarios. Ongoing research and continuous evaluation of clinical guidelines are essential endeavors to enhance our understanding of the most suitable technique for specific circumstances.